HUBUNGAN POSISI PERGELANGAN TANGAN SAAT MENGETIK TERHADAP RISIKO TERJADINYA CARPAL TUNNEL SYNDROME (CTS) PADA KARYAWAN PT. X - Made Adhi Dharma Setiawan; I Made Niko Winaya; I Made Muliarta (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2017)
ABSTRACTEmployees who operate computer and are typing on keyboard everyday have higher risk of wrist pain because of non-ergonomic work position. This study was conducted to assess the relationship between wrist position when typingand risk level of CTS (Carpal Tunnel Syndrome) in employees of PT.X. This study is an analytical observational studywith cross-sectional study design. The population in this study is the employee of PT.X. The sample consists of 66people. The subjects are 30-50 years old men and women who have been working for more than a year. The testsused in this research are bivariate analysis Pearson Product Moment and univariate analysis. The result shows that15 of 66 employees (22,7%) have good postures and 51 of 66 employees (77,3%) have bad work postures. 39 of 66employees (59,1%) have risk of CTS and 27 of 66 employees (59,1%) do not have risk of CTS. The final result of ChiSquare Test shows the significance of 0,000 (p<0,05). The result of the statistic tests shows that wrist position whentyping has significant relationship with the risk of CTS (Carpal Tunnel Syndrome).Keywords : Wrist Position, Employees, Carpal tunnel syndrome.